Work-life balance and employees’ commitment in plastics manufacturing firms in Anambra State, Nigeria - Kekeocha, Mary Ezinne; Anoke, Amechi Fabian; Chukwuemeka-Onuzulike, Nkechi; Ngozi, Nzewi Hope (Goodwood Publishing, 2023)
Purpose: This study aims to determine the correlation between work-life balance and employee commitment in plastic manufacturing firms in Anambra State, Nigeria. Research Methodology: A descriptive survey design was employed, the questionnaire was used to elucidate information from respondents while regression analysis was used to test the stated hypotheses and determine the relationships between the variables in the study. Results:–life balance-continuance commitment had a positive but minor impact on employees' commitment, normative commitment had a substantial negative influence on employees' commitment, and affective commitment had a strong positive relationship with employees' dedication. Limitations: This study was limited to plastic manufacturing firms in Anambra State, Nigeria. It is expected that the financial and health sectors, which are known to have stiff working conditions, should be researched to support or contradict this current finding. Contribution: This study is expected to serve as a working tool for SME operators, manufacturing firms, policymakers, and the government, as offering a healthy work-life balance can be a significant factor in attracting top talent.